2021
DOI: 10.1002/er.6416
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of energy conversion efficiency and thermal reliability of novel, unileg segmented thermoelectric generation systems

Abstract: Despite their great potential to recover waste heat, thermoelectric generators (TEGs) find limited usage since thermoelectric materials are only efficient within a limited temperature range. Using multiple materials in segmented TEGs can significantly enhance the overall energy conversion efficiency. However, thermal reliability is questionable in these systems especially at elevated temperatures and in annular configurations. This study explores the feasibility of utilizing unileg (single material) segmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The power was measured only for a small single leg, so that the result showed low power output at small ΔT (8K), which indicates a measurable power that can be obtained for ΔT above 8 K. The numerical simulation curves generated by ANSYS numerical model, a three-dimensional, 20-node coupling elements SOLID226 were selected to simulate the TE current and voltage, similar to the reference studies reported. [42][43][44][45] A single circular leg module with its dimensions was used for TE power calculations as shown in Figure 7F. Finally, it can be concluded that the numerical simulation curves are in good agreement with the experimental results.…”
Section: Power Generation Characteristicsmentioning
confidence: 60%
“…The power was measured only for a small single leg, so that the result showed low power output at small ΔT (8K), which indicates a measurable power that can be obtained for ΔT above 8 K. The numerical simulation curves generated by ANSYS numerical model, a three-dimensional, 20-node coupling elements SOLID226 were selected to simulate the TE current and voltage, similar to the reference studies reported. [42][43][44][45] A single circular leg module with its dimensions was used for TE power calculations as shown in Figure 7F. Finally, it can be concluded that the numerical simulation curves are in good agreement with the experimental results.…”
Section: Power Generation Characteristicsmentioning
confidence: 60%
“…The experimental results were also validated by generating numerical simulation curves ( Figure 5 a–f). These curves were generated by a three-dimensional ANSYS numerical model with 20 node coupling elements, SOLID226, selected to simulate the thermoelectric current and voltage, similar to the work reported in the literature [ 48 , 49 , 50 , 51 ]. More details about this model are described in the Supplementary Data .…”
Section: Resultsmentioning
confidence: 99%
“…Thermoelectric performance can be characterized by the dimensionless thermoelectric figure‐of‐merit ZT , which is expressed as ZT = α 2 σ Τ /( κ L + κ c ), where α , σ , κ c , κ L , and T represent Seebeck coefficient, electrical conductivity, carrier thermal conductivity, lattice thermal conductivity, and absolute temperature, respectively [5] . ZT value largely determines the efficiency of power generation and thermoelectric refrigeration [5–8] . Therefore, increasing ZT is a key in thermoelectric materials research [3,9,10] …”
Section: Introductionmentioning
confidence: 99%